The role of the child’s theater in promoting national identity in early childhood according to the Kingdom’s vision 2030 from the point of view of teachers - Alharbi, Atheer Khudhayr (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to reveal the role of the child’s theater in promoting national identity for children in early childhood in accordance with the Kingdom of Saudi Arabia’s 2030 vision from the teachers’ point of views. For achieving this aim, the study used the descriptive method while using a questionnaire as a data collection method with sample of (146) teachers in kindergartens in Hafr Al-Batin. The study used the questionnaire in knindergarteen and reached the following results: from kindergarten teachers especially in preparing for the theater, such as… was in a very large degree. As for participants’ viewpoints of the good specifications of the content presented in the child’s theater was in a very large degree, and the impact of the child’s theater on the formation of identity among children in the early childhood stage from the teachers' point of view is very large. In the light of these findings, the researcher recommended directing specialists in the field of early childhood to the need to pay attention to the child's theater because of its effective role in strengthening the national identity.
Keywords: Children's theatre; strengthening the national identity; the Kingdom's vision 2030